The Gcn4 transcription factor reduces protein synthesis capacity and extends yeast lifespan - Nitish Mittal (Nature Portfolio, 2017)
The transcription factor Gcn4 is known to regulate yeast amino acid synthesis. Here, the authors show that Gcn4 also acts as a repressor of protein biosynthesis in a range of conditions that enhance yeast lifespan, such as ribosomal protein knockout, calorie restriction or mTOR inhibition.